DEVELOPMENT OF RADIAL AERODYNAMIC SWIRLERS (Jurnal Mekanikal, 2018)
Experimental studies show that swirl has large-scale effects onflowfields: jet growth. entrainment and decay (for isothermalflows) and flame size, shape. stability and combustion intensity(for combustion flows) are affected by the degree of swirl imparted to the flow. This degree of swirl is usually characterised by the nondimensional number representing theratio ofaxial flux ofswirl momentum to the axial flux of axialmomentum times the equivalent nozzle radius. This parameter.denoted by the symbol S. is called the swirl number and hasbeen used extensively to designate the strength of the swirl.This paper is to review the aerodynamics of swirling flow incombustion system.
Keywords: Keywords